Human Resource Ethical Dilemmas in Healthcare - Gauri Pande (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
Human Resource departments are critical departments for any organization as they ensure compliance with the code of conduct. Actions and decisions taken by the employee of an organization directly impact the reputation of an organization. In healthcare, the role of HR director is amplified due to the high sensitivity of institutions' nature and objectives in this sector. Hospitals and other healthcare centers directly deal with people seeking healthcare services. Therefore, slight violations of the code of conduct by the service providers can have a critical impact on health of the people at the healthcare service center. This paper sheds light on ethical dilemmas commonly faced by HR managers in the healthcare sector and their practices to manage those issues. The study comprises three parts where the initial section extends the discussion on ethics associated with general HR operations with a focus on the healthcare industry. It is followed by comparing different modes of handling ethical dilemmas while proceeding with the image restoration strategy. Then, some empirical evidence of managing ethical crises is covered to check the practical application of learned theoretical ideas. Finally, some conclusive opinions and recommendations are outlined based on the core findings of the study